Functional verification and characterization of a type-III geranylgeranyl diphosphate synthase gene from Sporobolomyces pararoseus NGR - Yan, Jianyu; Li, Chunji; Zhang, Ning; Li, Chunwang; Wang, Yunjiao; Li, Bingxue (Frontiers in Microbiology, 2022)
Carotenoids, a group of natural pigments, have strong antioxidant properties and act as precursors to vitamin A, which have garnered attention from industry and researchers. Sporobolomyces pararoseus represents a hyper-producer of carotenoids, mainly including β–carotene, torulene and torularhodin. Geranylgeranyl diphosphate synthase (GGPPS) is regarded as a key enzyme in the carotenoid biosynthesis pathway. However, the precise nature of the gene encoding GGPPS in S. pararoseus has not been reported yet. Here, we cloned a cDNA copy of the geranylgeranyl diphosphate synthase protein-encoding gene crtE from S. pararoseus NGR. The crtE full-length genomic DNA and cDNA are 1722 bp and 1134 bp respectively, which consist of 9 exons and 8 introns. This gene encodes 377 amino acids protein with a predicted molecular mass of 42.59 kDa and a PI of 5.66. Identification of the crtE gene encoding a functional GGPPS was performed using heterologous complementation detection in Escherichia coli. In vitro enzymatic activity experiments showed that CrtE utilized farnesyl diphosphate (FPP) as an allylic substrate for the condensation reaction with isopentenyl diphosphate (IPP), generating more of the unique product GGPP compared to other allylic substrates. The predicted CrtE 3D-model was analyzed in comparison with yeast GGPPS. The condensation reaction occurs in the cavity of the subunit, and three bulky amino acids (Tyr110, Phe111 and His141) below the cavity prevent further extension of the product. Our findings provide a new source of genes for carotenoid genetic engineering.